Preparation of aromatic polyamidines and their transformation in polybenzimidazoles - B. Ch. Kholkhoev; V. F. Burdukovskii; D. M. Mognonov (eXPRESS Polymer Letters, 2014)
Polymers with amidine groups –NH–C(=NH)– in main chain were synthesized by two different approaches. The first strategy consists in polyaddition of dinitriles and diamines in acidic ionic liquids (ILs) which act as catalyst and solvent, while the second approach is based on polycondensation of 4,4'-oxybis(benzoic acid) diamide and diamines in Eaton’s reagent (ER). The resulting polyamidines (PADs) with Mw up to 25 000 g/mol possess thermal stability on air up to 288°C, and good solubility in polar organic solvents. Moreover dehydrocyclization of obtained PADs into polybenzimidazoles (PBIs) under the action of various oxidants was also studied in this work. The crosslinked films based on PBI and poly(amino imide) resin (PAIR) possess high mechanical characteristics. It has been proved that the crosslinked films based on PBI matrix are perspective materials for design the phosphoric acid electrolyte membranes for the medium temperature fuel cells.